Enhancing quantity and quality academic papers through collaborative training between Universitas Negeri Jakarta and Universitas Malaysia Sabah - Suherman Suherman; Agus Wibowo; Dwi kismayanti respati; Tri Hesti Utaminingtyas; Gentiga muhammad zairin; Rr. Ponco Dewi Karyaningsih; Etty Gurendrawati; Lim Thien Sang (Universitas Negeri Malang, 2023)
Publication is one of the efforts to increase the competitiveness of higher education institutions. The competitiveness of tertiary institutions can be seen from the number of scientific publications produced. The more productive universities produce scientific publications, the higher their competitiveness. This community services activity is one of the Tri Dharma tasks where lecturers can explore themselves and socialize with the community. Community service activities aim to increase lecturers’ knowledge and understanding of publications in reputable international journals. This training activity was carried out by the Faculty of Economics, Universitas Negeri Jakarta (FEUNJ), and the Faculty of Business, Economics, and Accounting, Universiti Malaysia Sabah (FBEA UMS). The participants in this activity were lecturers at FEUNJ and FBEA UMS. The results of this activity show an increase in the knowledge and skills of the trainees in producing international-quality articles. This paper can complement the existing literature, especially related to international collaborative community services